Factors Supporting the Success of the Whistleblowing System in Public Sector: Case Study of the Institution XYZ - Basrifan Arief Bakti; Dwi Hartanti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
To achieve good and clean governance, good governance is required. One of the supporting instruments is the whistleblowing system. However, there are still many cases of fraud in the public sector. This final paper aims to analyze the whistleblowing system or the complaint handling system in the Institution XYZ, which is one of the Government Internal Supervisory Apparatuses (APIP). This final work uses qualitative and descriptive analytical methods. The instruments used are interviews and questionnaires. The results of the study indicate that although the implementation of the whistleblowing system at Institution XYZ has been adequate, there are still some weaknesses. These weaknesses include the presence of employees who do not want to take advantage of the whistleblowing system and the provision of award the whistleblower. This research also provides suggestions for improving the implementation of the whistleblowing system at Institution XYZ in the future.